Analysis of Figurative Language on “Tua Kalok Ceremony” - Maria Fatima (UPT Publikasi dan Penerbitan Universitas San Pedro, 2023)
This research aims to identify and analyze the meaningof figurative language on tua kalok ceremony.The researcher used qualitative method. Data collection techniques used in this research used, interview and documentation.In the results there are process of tua kalok ceremony,in the process of Tua Kalok Ceremony have three stages are the preparation stage of the ritual, the main stage, and the final stage and the kind of figurative language found in Tua Kalok ceremony is synecdoche,personification and repetition, one of the meaning on figurative language found in Tua Kalok ceremony is Synecdoche,example Mai ita tinu Tua Supan widin jajin nan or Let us drink tua and mixed in goat's blood,the meqaning that let us drink tua mixed with goat's blood, which symbolizes taking the traditional oath.